Can the Internet Forget? – Rhe Eight to be Forgotten in the EU Law and its Actual Impact on the Internet. Comparison of the Approaches Towards the Notion and Assessment of its Effectiveness - Gebuza, Aleksandra (University of Wroclaw. Faculty of Law, Administration & Economics, 2019)
The main aim of the article is to provide analysis on the notion of the right to be forgotten developed by the CJEU in the ruling Google v. AEPD & Gonzalez and by the General Data Protection Regulation within the context of the processing of personal data on the Internet. The analysis provides the comparison of approach towards the notion between European and American jurisprudence and doctrine, in order to demonstrate the scale of difficulty in applying the concept in practice.
Keywords: the right to be forgotten; Google v. AEPD & Gonzalez case; the freedom of speech; the right to privacy; search engines; General Data Protection Regulation